De l’histoire numérique à l’histoire données ? - Cédric du Mouza; Stéphane Lamassé; Philippe Rygiel (Les Cahiers de Framespa)
Historians have been rigorously producing and analyzing information long before the emergence of big data and the digital age. However, the current transformations, which see the accumulation of large deposits of historical data, create new challenges and opportunities that we return to here. Indeed, the field of historical sciences lacks a strict formalization of data characteristics, and no taxonomy or systematic reflection on the nature of data has been established or published. From ongoing work, following on from previous undertakings, the authors show that a formalization of data that integrates the conditions of their production and a link to documentary apparatus, which is only possible thanks to effective collaboration with practitioners from other disciplines, enriches the interpretation of historical data while producing knowledge effects as to their nature and giving rise to fruitful questions for computer scientists relating to the consideration of data quality.